Cultural urban landscapes, a legacy to preserve - Zárate Martín, M. Antonio (Anales de Geografía de la Universidad Complutense, 2010)
The literature, the engraving and the painting help to define as “cultural” the urban landscapes that stand out for his emplacement, environment, studding and constructions; definitively, for everything what patrimonial value awards them and reflects manners of life that have happened across the time. Because of it, the “cultural urban landscapes ” are privileged elements that allow the reading of the past, are the best collective image of his cities and enclose a didactic value for the society. In this article ensued from a project of investigation subsidized by the AECI, there are analyzed the mechanisms that favor the transformation of the cultural landscapes and the difficulties of preserving them. Few of these landscapes have come up to us well preserved, in spite of the fact that the worry for the patrimony is ancient and of that the references to the landscape are gathered in the whole planning. The “Convention of the European Landscape” is the principal hopes to harmonize landscape and patrimony